AMBIGUITAS INFORMASI PADA TUTURAN ANAK BILINGUAL (KAJIAN SOSIOPRAGMATIK) - Aprilia, Nabila Intan; Rumilah, Siti (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to educate parents of bilingual children to pay attention to their child's language learning environment and understand the syntax of their speech. This research is descriptive qualitative in nature using listening, involving, speaking data collection techniques. Data analysis includes identification, classification and description. The research results show that based on Krashen's theory, children's B2 learning and acquisition, in this case RSA, comes from formal language environment (educational settings) and informal language environment such as play situations, family interactions (especially with mothers), the influence of devices. and other people. According to Bloom, the relationship between grammar and information expresses a situation that corresponds to a combination of words from RSA.